On Convergent Filters in Soft Topological Spaces - Rashed , Rukaia Mahmoud Mohammed (Scientific Journal of University of Benghazi, 2024)
This study explains the concept of soft topological spaces in the view soft filters, studying the properties of soft filters in soft topological spaces. The study aims to contribute to the development of soft mathematical concepts and structures, building on the foundations of soft set theory. During the study, we found a relation between the concepts -convergence and -Hausdorff soft topological spaces.